The Marketization of Religion: Field, Capital, and Consumer Identity - McAlexander,Jim; DuFault,Beth; Martin,Diane; Schouten,John (Journal of Consumer Research, 2014)
Certain institutions traditionally have had broad socializing influence over their members, providing templates for identity that comprehend all aspects of life from the existential and moral to the mundanely material. Marketization and detraditionalization undermine that socializing role. This study examines the consequences when, for some members, such an institution loses its authority to structure identity. With a hermeneutical method and a perspective grounded in Bourdieus theories of fields and capital, this research investigates the experiences of disaffected members of a religious institution and consumption field. Consumers face severe crises of identity and the need to rebuild their self-understandings in an unfamiliar marketplace of identity resources. Unable to remain comfortably in the field of their primary socialization, they are nevertheless bound to it by investments in field-specific capital. In negotiating this dilemma, they demonstrate the inseparability and co-constitutive nature of ideology and consumption.
Keywords: Marketing